IMPROVING STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT BY APPLYING PREDICTION STRATEGY - Hastati Perangin-angin; Meisuri (Universitas Negeri Medan, 2013)
This study attempted to improve students’ reading comprehension indescriptive text by applying prediction strategy. This study was conducted byusing classroom action research. The subject of this research was class X-1 SMANegeri 1 Kisaran which consisted of 34 students. The research was conducted intwo cycles and every cycle consisted of three meetings. The instruments forcollecting data were taken from quantitative data and qualitative data. Thequantitative data were taken from the reading test (multiple choice test consistedof 25 questions). The qualitative data were taken from diary notes, observationsheet and interview sheet. Based on reading test scores, students’ score keptimproving in every test. In the orientation test the mean was 53.41, in the cycle Itest the mean was 67.52 and in the cycle II test the mean was 83.52. Based ondiary notes, observation sheet and interview sheet, it was found that teachinglearning process run well. Students were active, enthusiastic, and interested inreading. The result of the research showed that prediction strategy significantlyimproved students’ reading comprehension in descriptive text.